Adaptation issues of machine learning in safety digitization - Gyana Ranjana Panigrahi; Nalini Kanta Barpanda; Komma Anitha; Shanti Rathore; Preesat Biswas; Prabira Kumar Sethy (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The internet community is the only set of irreplaceable spaces in today’s world and is used by millions for knowledge acquittance via the digital exchange between the landed gentry. The torrent of available e-contents in the Internet community attracts corporates and researchers to find the factual weightage of formed data. It is high time for digital diversification, which is the objective of using various learning-based machine learning (ML) systems for hands-on fortification. The main idea is to make stylistic communication more understandable. Here, the authors try to adapt the factual weightage procedure of formed data through the Internet community using machine learning schemes. Hence, the authors have chosen to emphasize cyber security, which is not well discussed and concerned with ethical contemplation from hackers' forums amidst internet communities. There are disparities in the continual growth of connotations, acronyms, spellings, and even technical jargon, which need periodic re-learning and their prototype implications through the proposed model.